IMPLEMENTASI KURIKULUM ISMUBA DI SD MUHAMMADIYAH KARANGKAJEN YOGYAKARTA - Wasito, Wasito (Jurnal Pendidikan Islam, 2019)
The purpose of this study was to describe the implementation of the ISMUBA curriculum at Muhammadiyah Elementary School Karangkajen Yogyakarta. This study uses qualitative research. The location of this research at Muhammadiyah Elementary School of Karangkajen Yogyakarta. The data were collected through observation, interviews, and documentation. Data analysis conducted by researchers is to use inductive methods, namely the process of analyzing based on existing data or obtained later developed with certain patterns with the stages of reducing data, presenting data, and drawing conclusions. The results of the study shows that the implementation of the ISMUBA Curriculum at Muhammadiyah Elementary School in Karangkajen Yogyakarta as a whole meet the curriculum implementation standards. The disadvantage is consistency and continuity in implementation, then human Resources is not evenly distributed in quality. Another thing is that the habitual character becomes very strong like getting used to prayer in congregation and alms.